A new method for studying the 3D transient flow of misaligned journal bearings in flexible rotor-bearing systems - Li, Qiang; Liu, Shu-lian; Pan, Xiao-hong; Zheng, Shui-ying (Journal of Zhejiang University. A. Science, 2012)
The effects ofjournal misalignment on the transient flow of a finite grooved journal bearing are presented in this study. A new 3D computational fluid dynamics （CFD） analysis method is applied. Also, the quasi-coupling calculation of transient fluid dynamics：of oil film in journal bearing and rotor dynamics is considered in the analysis. Based on the structured mesh, a new approach for mesh movement is proposed to update the mesh volume when the journal moves during the fluid dynamics simula- tion of an oil film. Existing dynamic mesh models provided by FLUENT are not suitable for the transient oil flow in journal bearings. The movement of the journal is obtained by solving the moving equations of the rotor-bearing system with the calculated film pressure as the boundary condition of the load. The data exchange between fluid dynamics and rotor dynamics is realized by data files. Results obtained from the CFD model were consistent with previous experimental results on misaligned journal bearings Film pressure, oil film force, friction torque, misalignment moment and attitude angle were calculated and compared for mis- aligned and aligned journal bearings. The results indicate that bearing performances are greatly affected by misalignment which is caused by unbalanced excitation, and the CFD method based on the fluid-structure interaction （FSI） technique can effectively predict the transient flow field ofa misaligned journal bearing in a rotor-bearing system.